Wpływ uprawiania sportu kajak polo na ruchomość stawu ramiennego. Badania pilotażowe = The influence of sport canoe polo on the mobility of the shoulder joint. The pilot studies - Ewa Grygierzec; Małgorzata Szczotka; Ewa Śmieciuch; Tomasz Łosień (Journal of Education, Health and Sport, 2016)
Grygierzec Ewa, Szczotka Małgorzata, Śmieciuch Ewa, Łosień Tomasz. Wpływ uprawiania sportu kajak polo na ruchomość stawu ramiennego. Badania pilotażowe = The influence of sport canoe polo on the mobility of the shoulder joint. The pilot studies. Journal of Education, Health and Sport. 2016;6(7):130-137. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57295